Experience-dependent plasticity in white matter microstructure: reasoning training alters structural connectivity - Mackey, Allyson P.; Whitaker, Kirstie J.; Bunge, Silvia A. (Frontiers in Neuroanatomy, 2012)
Diffusion tensor imaging (DTI) techniques have made it possible to investigate white matter plasticity in humans. Changes in DTI measures, principally increases in fractional anisotropy (FA), have been observed following training programs as diverse as juggling, meditation, and working memory. Here, we sought to test whether three months of reasoning training could alter white matter microstructure. We recruited participants (n = 23) who were enrolled in a course to prepare for the Law School Admission Test (LSAT), a test that places strong demands on reasoning skills, as well as age- and IQ-matched controls planning to take the LSAT in the future (n = 22). DTI data were collected at two scan sessions scheduled three months apart. In trained participants but not controls, we observed decreases in radial diffusivity (RD) in white matter connecting frontal cortices, and in mean diffusivity (MD) within frontal and parietal lobe white matter. Further, participants exhibiting larger gains on the LSAT exhibited greater decreases in MD in the right internal capsule. In summary, reasoning training altered multiple measures of white matter structure in young adults. While the cellular underpinnings are unknown, these results provide evidence of experience-dependent white matter changes that may not be limited to myelination.